HUBUNGAN DUKUNGAN KELUARGA TERHADAP PEMENUHAN ADL PADA PASIEN PASCA STROKE DI DUSUN TAMBAK BAYAN, BABARSARI, SLEMAN, D.I YOGYAKARTA - Thomas Aquino; Antok Nurwidi Antara; Aris Budi Pratama (STIKES Wira Husada Yogyakarta, 2018)
Background: Stroke is the leading cause of death in the world. The main is the presence of hypertension or high blood pressure is usually caused by excessive stress or something surprising. Often a stroke followed by a psychological disorder including self concept disorder is caused due to the patient’s inability to do something usually done before a stroke. Therefore, the role of the family in the rehabilitation or recovery of family members with post-stroke is needed, including the fulﬁ llment of basic needs of patients and also their psychological needs. Objective: To know the relationship of family support to the fulﬁ llment of ADL in post-stroke patient in Tambak Bayan hamlet, Babarsari, Sleman, D.I YogyakartMethod: This research is descriptive analytic research using Cross Sectional .The subjects of this study were post-stroke patients in Tambak Bayan hamlet, Babarsari, Sleman, D.I Yogyakarta, amounting to 32 people. Sampling technique using Total Sampling method.Results: The results of this study indicate that family support is in good ie 24 respondents or 75% with ADL fulﬁ llment 65,6% (enough). Chi square correlation test between family support relationship to post-stroke patient ADL fulﬁ llment in Tambak Bayan hamlet, Babarsari, Sleman, D.I Yogyakarta is known sig 0,000 which means there is correlation with strong Correlation Coefﬁ cient (0.722).Conclusions: There is a signiﬁ cant relationship between family support for ADL post-stroke patient fulﬁ llment.